Understanding the role of peer pressure on engineering students' learning behavior: A TPB perspective - Xu, Lin; Zhang, Jingxiao; Ding, Yiying; Zheng, Junwei; Sun, Gangzhu; Zhang, Wei; Philbin, Simon P. (Frontiers in Public Health, 2023)
This study aims to explore the influence of engineering students’ peer pressure on learning behaviour based on the theory of planned behaviour (TPB). In addition to attitudes, subjective norms, and perceived behavioural controls inherent in TPB, two new dimensions---gender difference and peer academic ability---were incorporated to construct a framework of the dimensions of peer pressure as affecting engineering students as well as an expanded model of TPB. A questionnaire survey was conducted with 160 college engineering students and a structural equation model (SEM) was used to test the hypotheses. The results found that positive peer pressure enhances the motivation to learn among engineering students, which in turn drives learning behaviour. This research yields theoretical and practical contributions, which identify that the TPB can predict engineering students’ learning behaviour under peer pressure. The study also expands and reshapes the attitude relationship of the TPB, and enhances the explanatory strength of the model. This is valuable for engineering education since this helps engineering students to enhance their comprehensive skills-set and become more capable in the digital era.